Clinical Outcomes of IgG4-Related Ophthalmic Disease and Idiopathic Sclerosing Orbital Inflammation. Issue 1 (26th March 2021) - Son, Ki Young; Woo, Kyung In; Kim, Yoon-Duck
Abstract : Purpose: To compare the clinical features, treatment outcomes, and prognoses of immunoglobulin G4-related ophthalmic disease (IgG4-ROD) and idiopathic sclerosing orbital inflammation (ISOI). Methods: This retrospective case series included 40 and 22 biopsy-proven cases of IgG4-ROD and ISOI, respectively. The authors reviewed medical charts and images to determine the clinical presentation, involvement pattern, and treatment outcomes. The main outcome measures were differences in disease manifestation, treatment modalities and efficacy, medication-free remission rate, and predictive factors for remission. Results: The median ages were 51 (range 31–72) and 39 (range 9–73) years in the IgG4-ROD and ISOI groups, respectively. The most frequently involved sites were the lacrimal gland (39 cases, 98%) in IgG4-ROD patients and the extraconal region (15 cases, 68%) in ISOI patients. No significant difference was observed in the initial treatment response between the groups. Medication-free remission was achieved in 22 (55%) IgG4-ROD patients and 10 (45%) ISOI patients; none of the IgG4-ROD patients showed permanent ocular dysfunction, while half of the ISOI patients had permanent visual loss or limited ocular motilities. Multivariate analysis indicated that extraocular muscle enlargement (odds ratio, 0.11; 95% confidence interval, 0.01–0.98) and IgG4:IgG ratio on histopathology (odds ratio, 0.08; 95% confidence interval, 0.01–0.86) were negatively associated with medication-free remission in IgG4-ROD patients. Conclusions: Although IgG4-ROD and ISOI share common histological findings of mass-forming sclerosis, IgG4-ROD frequently has a more indolent clinical course, whereas ISOI often demonstrates a more aggressive clinical course, resulting in ocular dysfunction even after remission. Different pathogeneses may account for the different disease characteristics. Abstract : IgG4-related ophthalmic disease and idiopathic sclerosing orbital inflammation have different clinical characteristics, treatment outcomes, and prognoses, indicating that the 2 diseases have different pathogeneses or disease-modifying processes.